Pengaruh Kualitas Pelayanan, Persepsi Harga dan Cita Rasa terhadap Kepuasan Konsumen Jus Buah Segar & Sup Buah Sendy - Nabila Aisyatur Rahmah; Muhammad Alhada Faudilah Habib (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Sendy’s Fresh Fruit Juice & Fruit Soup is an MSME business operating in the culinary and beverage sector that has developed in Gresik City. In the midst of a lot of competition with similar beverage products, Sendy's Fresh Fruit Juice & Fruit Soup is able to compete in sales and earn profits that continue to increase. The aim of this research is to determine the influence of service quality, price perception and taste on consumer satisfaction with Sendy's Fresh Fruit Juice & Fruit Soup. The population in this study were consumers of Sendy's Fresh Fruit Juice & Fruit Soup. The method used in this research is quantitative with an associative type of research. This research used an accidental sampling method with 100 respondents. The data sources used in this research are primary data and secondary data. With the help of the IBM SPSS 23 application, the research results show that: (1) service quality, price perception and taste have a significant effect on consumer satisfaction in the Sendy Fresh Fruit Juice & Fruit Soup business, (2) service quality has a positive and significant effect on satisfaction consumers in the Sendy Fresh Fruit Juice & Fruit Soup business, (3) price perception has a positive and significant effect on consumer satisfaction in the Sendy Fresh Fruit Juice & Fruit Soup business, (4) taste has a positive and significant effect on consumer satisfaction in the Fresh Fruit Juice business & Sendy Fruit Soup.